ESTIMASI TINGKAT KEKRITISAN LAHAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN TANJUNG SELOR, KABUPATEN BULUNGAN (JURNAL SPASIAL, 2019)
Based on data obtained from the Regional Environmental Status (SLHD) of North Kalimantan in 2016 noted, the area of critical land in the province of North Kalimantan reached 124,993,532 hectares (Ha). This amount accounts for around 0.53 percent of the total national degraded land which reaches 24 million hectares. The area of critical land in Bulungan Regency is 7,398.22 Ha, and has land with a very critical status of 232.68 Ha. This shows that critical land has occurred in almost all regions of Bulungan Regency. The purpose of this study was to determine the extent of the level of land criticality in the Tanjung Selor Subdistrict. The method used is spatial analysis of various parameters using geographic information systems. The results of mapping of critical land classes in Tanjung Selor Subdistrict obtained that Critical Land 33.96 Ha (0.06%), Critically Fair Land 4,747.49 Ha (8.87%), Critical Potential Land 39,860.11 Ha (74.45%) and Non Critical Land 8,898 Ha (16.62%)